Sweet spot areas for shale oil and shale gas plays in the Upper Cretaceous rocks of the Middle Magdalena Valley, Colombia: insights from basin modeling - Pastor-Chacón, Andrés; Aguilera, Roberto; Triana, Jorge Luis; Paez-Reyes, Manuel; Cantisano, Maria; Bravo, Luis; Gamba, Néstor; Niño, Miled; Delgado, Alexandra; Mendoza, Gabriel; Rodriguez, Juan David; Romero-Ballén, Oscar; et al. (Frontiers in Earth Science, 2023)
The Middle Magdalena Valley Basin (MMVB) in Colombia has a long history of conventional hydrocarbon exploration and production, with a cumulative production of 2.75 billion barrels of oil as of December 2021. Recent interest has been directed towards unconventional hydrocarbon plays within the basin due to the fine-grained nature of its Cretaceous source rocks and their mineralogy and mechanical properties. This study presents a three-dimensional basin model for three Upper Cretaceous source rocks, known as the "La Luna Formation," within the MMVB. The model was developed using new data from five outcrops, 7,640 km of 2D seismic lines, and forty-one boreholes, as well as additional data sets such as X-ray diffraction analyses, pyrolysis analyses, well-log correlations, facies analysis, fracture pattern prediction, pore pressure analysis, heat flow estimations, and petrophysical data. The model estimates total retained oil and gas volumes to be 7.95 billion barrels and 4.21 trillion cubic feet in most probable scenarios, after a 15% recovery factor. Seismic interpretation reveals pre-Eocene structures beneath Paleogene and Neogene sediments, and the thickness variation of the source rocks from south to north of the basin. Petrophysical modeling shows effective porosities ranging from 2-12% and organic porosities lower than 0.1%, with parts of the succession that might correspond to a carrier bed play. From a geomechanical perspective, we identified several brittle strata based on the higher concentrations of carbonates and quartz, and the areas with a higher probability of occurrence of natural fractures. Pore pressure analysis of multiple wells shows that wells in which the Middle Eocene unconformity has beveled the source rocks have no sealing capacity, becoming a risk for the play. The results suggest potential for unconventional hydrocarbon plays in the MMVB, with sweet spot areas being primarily controlled by porosity, thermal maturity, gas-oil ratios, and retained oil and gas volumes, as well as to a lesser degree, the probability of natural fractures and pore pressure conditions. However, further exploration is needed to constrain uncertainties regarding facies and source rock quality, particularly within the depocenters of the basin, in order to prove the economic feasibility of these unconventional plays.